Genetic polymorphisms of glutathione S transferase and cervical intraepithelial neoplasia - Daniel Mureșan; Cătană Andreea; Popp Radu Anghel; Dumitraș Diana Elena; Stamatian Florin; Buzoianu Anca Dana; Rotar Ioana Cristina (Romanian Journal of Laboratory Medicine, 2016)
Aim: The present study aim to analyze the relationship between GST M/T genotypes of glutathione S-transferases and cervical intraepithelial neoplasia.